Scoping Review: Hubungan Berat Badan Lahir Rendah (BBLR) dengan Keterlambatan Motorik Kasar pada Anak Usia Nol sampai Dua Tahun - Habib Syarif Hidayatuloh; Cice Tresnasari; Hana Sofia R (UNISBA Press, 2022)
Abstract. Gross motor development is regulated by the cerebral cortex which controls large muscle groups and functions to coordinate body movements during activities. The development period from zero to two years is a golden period of child development, including motor development. Delays in gross motor development are delays in coordination of large muscles, bones, and nerves. Several internal risk factors have been associated with gross motor delay, such as microcephaly, prematurity, and low birth weight (LBW). The purpose of this study was to analyze the relationship between LBW and the incidence of gross motor delay in children aged zero to two years. This research is a scoping c review, by searching for articles from the PubMed, SpringerLink, ProQuest, and Science Direct databases. Articles that fit the inclusion criteria were 959 articles and those included in the exclusion criteria were 955 articles. The results of the feasibility test based on PICOS and the critical review test were obtained as many as four articles. This research was conducted in the period of April 2021. The results of the study and analysis of four articles, it was found that two articles stated that there was a relationship between LBW children and delays in gross motor development. Another article stated that there was a significant relationship between very low birth weight in children and gross motor delay. On the other hand, another article stated that there was no significant relationship between low birth weight children and gross motor delay. The conclusion of this study is that children with low birth weight increase the risk of delayed motor development including gross motor skills. Abstrak. Perkembangan motorik kasar diatur oleh korteks serebral yang mengontrol kelompok otot besar dan berfungsi mengoordinasikan gerakan tubuh saat beraktivitas. Masa perkembangan usia nol sampai dua tahun merupakan periode emas perkembangan anak termasuk perkembangan motorik. Keterlambatan perkembangan motorik kasar adalah keterlambatan koordinasi otot besar, tulang, dan saraf. Beberapa faktor risiko internal memiliki hubungan dengan keterlambatan motorik kasar, seperti mikrosefali, prematuritas, dan berat badan lahir rendah (BBLR). Tujuan penelitian ini menganalisis hubungan BBLR dengan kejadian keterlambatan motorik kasar pada anak usian nol sampai dua tahun. Penelitian ini merupakan scoping review, dengan mencari artikel dari database PubMed, SpringerLink, ProQuest, dan Science Direct. Artikel yang sesuai dengan kriteria inklusi sebanyak 959 artikel dan yang termasuk dalam kriteria eksklusi sebanyak 955 artikel. Hasil uji kelayakan berdasark atas PICOS dan uji telaah kritis didapatkan sebanyak empat artikel. Penelitian ini dilakukan pada periode April 2021. Hasil telaah dan analisis dari empat artikel, didapatkan dua artikel menyatakan bahwa terdapat hubungan antara anak BBLR terhadap keterlambatan perkembangan motorik kasar. Satu artikel lain menyatakan memiliki hubungan bermakna antara berat badan lahir sangat rendah pada anak dan keterlambatan motorik kasar. Sebaliknya, satu artikel lain menyatakan tidak terdapat hubungan yang bermakna antara anak berat badan lahir rendah dan keterlambatan motorik kasar. Simpulan penelitian ini adalah anak dengan berat badan lahir rendah meningkatkan risiko keterlambatan perkembangan motorik termasuk motorik kasar.